RLC score (R status, lymphovascular invasion, C-reactive protein) predicts survival following radical cystectomy for muscle-invasive bladder cancer - Struck, Julian Peter; Hupe, Marie Christine; Heinisch, Annika; Ozimek, Tomasz; Hennig, Martin Johannes Peter; Klee, Melanie; von Klot, Christoph; Kalogirou, Charis; Kuczyk, Markus A.; Merseburger, Axel S.; Kramer, Mario W. (Aktuelle Urologie, 2021)
Background CRP-based scoring systems were found to correlate with survival in patients with urooncologic diseases. Our retrospective single-centre study aimed to confirm CRP as a prognostic parameter in patients with bladder cancer (BCa) undergoing radical cystectomy (RC) and, based on the findings, to develop our own outcome score for muscle-invasive bladder cancer (MIBC) patients undergoing RC in order to identify patients with a high risk of mortality.Material and methods A total of 254 patients who underwent RC at Hanover Medical School between 1996 and 2007 were reviewed with a follow-up until autumn 2013. The clinicopathologic parameters assessed included age, co-morbidities, pre-/postoperative serum levels of CRP, leukocytes, haemoglobin, creatinine, urinary diversion, tumour grading, staging, lymph node status, lymph node density (LND), lymphovascular invasion (LVI), metastases, and resection margin status. The Chi-square test was used for univariate analyses. Kaplan-Meier estimates and the log-rank test were used for survival analyses. Regarding outcome, overall survival (OS) was assessed.Results The multivariate analysis excluding lymph node (LN)-positive and metastatic patients at time of RC showed a significant association of R status (R; p < 0.001), LVI (L; p = 0.021) and preoperative CRP level > 5 mg/l (C; p = 0.008) with OS. Based on these parameters, the RLC score was developed. The median OS in the intermediate, high-risk and very high-risk groups according to the RLC score was 62, 22, and 6.5 months, respectively. The score had a high predictive accuracy of 0.752.Conclusion The RLC score identifies BCa patients at a higher risk of overall mortality after RC. Overall, our study supports the role of CRP in prognostic score models for BCa.
Keywords: bladder cancer; C-reactive protein; survival score; radical cystectomy; overall survival